Immune system markers of neuroinflammation in patients with clinical diagnose of neuromyelitis optica Marcadores imunológicos em pacientes com diagnóstico de neuromielite óptica - Soniza Vieira Alves-Leon; Maria Lucia Vellutini Pimentel; Gabrielle Sant'Anna; Fabíola Rachid Malfetano; Cláudio Duque Estrada; Thereza Quirico- Santos (Arquivos de Neuro-Psiquiatria, 2008)
Neuromyelitis optica (NMO) is an inflammatory, demyelinating disease of the central nervous system characterized by the association of a serious myelitis and unilateral or bilateral optic neuritis. The present study aimed to analyze the immunological parameters of NMO patients with diagnosis established based on Wingerchuck et al. (1999) criteria. Production of IgG and IgA antibodies to antigens of MBP, PLP 95-116, MOG 92-106, and the cytokines interleukin-4 (IL-4) and interferon-γ (INF-γ) were assessed by Elisa assay. The cohort was formed by 28 NMO patients and a matched healthy control group. NMO patients had significant high levels of IgG to MOG (p<0.0001), PLP (p=0.0002) and MBP (p<0.0001), and solely IgA to MBP (p<0.0001). INF-γ (p=0.61) levels were similar to healthy controls. Increased production of IL-4 (p=0.0084) indicates an important role for this cytokine in the activation of Th2 regulatory cells and of the IgA producers B lymphocyte indicating activation of humoral immunity. A neuromielite óptica (NMO) é doença inflamatória do sistema nervoso central, caracterizada por mielite aguda ou subaguda grave e neurite óptica unilateral ou bilateral. Este estudo objetiva analisar parâmetros imunológicos de pacientes com critérios de Wingerchuck et al. (1999) para NMO. O método de ELISA avaliou a produção de IgG e IgA para antígenos da proteína básica da mielina (MBP), o proteolipídeo (PLP) 95-116, a glicoproteina associada ao oligodendrócito (MOG) 92-106 e as citocinas interleucina-4 (IL-4) e interferon-gama (INF-γ). Foram incluνdos 28 pacientes com NMO pareados com controles saudáveis. Pacientes com NMO apresentaram níveis significativamente elevados de imunoglobulinas reativas dos isotipos IgG para MOG (p<0,0001), PLP (p=0,0002) e MBP (p<0,0001) e IgA somente para MBP (p<0,0001). Os níveis de INF-γ (p=0,61) foram semelhantes aos controles. A produção elevada de IL-4 (p=0,0084) indica papel importante na ativação de células regulatórias Th2 e linfócitos B produtores de IgA e da ativação da imunidade humoral.